Diffusion of a Social Norm: Tracing the Emergence of the Housewife in the Netherlands, 1812-1922 - Frans W.A. van Poppel; Hendrik P. van Dalen; Evelien Walhout (Tinbergen Institute, 2006)
The emergence of the housewife in the Netherlands over the period 1812-1922 was strongly influenced by the social norm that women should withdraw from the labour market on the eve of marriage. Adherence to this norm is most clearly reflected in the emergence of the housewife among the lower classes, especially at the close of the nineteenth century among wives of farmers. Women in urban municipalities, however, set the norm far earlier and differences across social classes were significantly larger in towns than in rural areas. Paradoxically, the rise of the housewife did not change work pressures for lower–class women. This paradox is resolved by noting that they substituted registered work for unregistered work, e.g., in house industries, working in the family firm or farm.
Keywords: D13; J12; J16; N34; 330; marriage; norms; division of labour; housewife; breadwinner